Pivotal mental states - Brouwer, Ari; Carhart-Harris, Robin Lester (Journal of psychopharmacology (Oxford), 2021)
This paper introduces a new construct, the 'pivotal mental state', which is defined as a hyper-plastic state aiding rapid and deep learning that can mediate psychological transformation. We believe this new construct bears relevance to a broad range of psychological and psychiatric phenomena. We argue that pivotal mental states serve an important evolutionary function, that is, to aid psychological transformation when actual or perceived environmental pressures demand this. We cite evidence that chronic stress and neurotic traits are primers for a pivotal mental state, whereas acute stress can be a trigger. Inspired by research with serotonin 2A receptor agonist psychedelics, we highlight how activity at this particular receptor can robustly and reliably induce pivotal mental states, but we argue that the capacity for pivotal mental states is an inherent property of the human brain itself. Moreover, we hypothesize that serotonergic psychedelics hijack a system that has evolved to mediate rapid and deep learning when its need is sensed. We cite a breadth of evidences linking stress via a variety of inducers, with an upregulated serotonin 2A receptor system (e.g. upregulated availability of and/or binding to the receptor) and acute stress with 5-HT release, which we argue can activate this primed system to induce a pivotal mental state. The pivotal mental state model is multi-level, linking a specific molecular gateway (increased serotonin 2A receptor signaling) with the inception of a hyper-plastic brain and mind state, enhanced rate of associative learning and the potential mediation of a psychological transformation.